2021
DOI: 10.3390/ijerph18147501
|View full text |Cite
|
Sign up to set email alerts
|

Critical Feminist Service-Learning: A Physical Activity Program in a Woman’s Prison

Abstract: In recent decades, increasing emphasis has been placed on the role of universities in ensuring inclusive and equitable quality education. Higher education strategies such as critical feminist service-learning (CFSL) can help achieve true university-community engagement to achieve social good while allowing students to develop academic competencies, values, and social responsibility. This study analyzes the impact of a university physical activity–based CFSL project implemented at a woman’s prison. The study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…With this information, our expectations as sports instructors were diluted and, little by little, we stopped planning and preparing physical activity sessions, which is actually not strange in prison (Devís-Devís et al, 2017). As reported by Hinojosa-Alcalde and Soler (2021) we also found it difficult to adjust the program for the needs and interest of women. Our stance towards these activities became more and more flexible, coming to improvise our performances and agreeing almost completely with the requests of our participants.…”
Section: The Sports Center: Uncertainty Tensions and A Whirlwind Of E...mentioning
confidence: 75%
“…With this information, our expectations as sports instructors were diluted and, little by little, we stopped planning and preparing physical activity sessions, which is actually not strange in prison (Devís-Devís et al, 2017). As reported by Hinojosa-Alcalde and Soler (2021) we also found it difficult to adjust the program for the needs and interest of women. Our stance towards these activities became more and more flexible, coming to improvise our performances and agreeing almost completely with the requests of our participants.…”
Section: The Sports Center: Uncertainty Tensions and A Whirlwind Of E...mentioning
confidence: 75%
“…Despite this, CFSL is the focus of research in different disciplines such as gender and women's studies (Clark-Taylor, 2017; Martin & Beese, 2016;Williams & Ferber, 2008), sociology (Kesler-Gilbert, 2010;Freude et al, 2019;Vergés-Bosch et al, 2021), information and communication technologies (Marr, 2014;Villacampa-Morales et al, 2020), biology and health sciences (Brigidi & Birosta, 2020;Maicas et al, 2020) Specifically, this article focuses on SL in PAS (Chiva-Bartoll & Fernández-Rio 2021), the results of which provide evidence of its transformative and activist potential for improving social justice and gender equity (Chiva-Bartoll et al, 2022;Santos-Pastor et al, 2020). However, research and outcomes under critical feminist connotations are still at an incipient stage (Clark-Taylor, 2017; Williams and Ferber, 2008), hence this lack of information Hinojosa-Alcalde & Soler-Prat, 2021). However, it can be affirmed that there is a body of research that supports and defends the potential of CFSL, as shown in Figure 2.…”
Section: Precedents Of Critical Feminist Service-learning: Approaches...mentioning
confidence: 99%
“…In turn, all the elements that make up the project and the components of the T-LP (reflection, roles, assessment, language, etc.) are analyzed and adapted under these critical-feminist premises (Eretzian-Smirles, 2011;Hinojosa-Alcalde & Soler-Prat, 2021;Vergés-Bosch et al, 2021). Elements such as recognition, achievement and monitoring of the program focus on the growth and empowerment of both parties (students and women we work with) and recognizing the activity conducted by its participants.…”
Section: Key Aspects Of Critical Feminist Service-learning In Physica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Las autorías que han estudiado el ApSCF o bajo una perspectiva de género o feminista, respaldan que permite estrechar los lazos entre la comunidad y la institución universitaria, incrementando los conocimientos específicos en materia de género, así como aquellos para contribuir a la justicia social (Hinojosa-Alcalde & Soler-Prat, 2021;Vergés-Bosch et al, 2021). El estudio de Jiménez-Millán et al (2020) muestra el desarrollo de una conciencia crítica, activa y responsable de las personas partícipes, para reprobar sesgos de género y modelos patriarcales, incrementando sus habilidades comunicativas, de agencia o empoderamiento.…”
unclassified